2002
DOI: 10.1103/physrevlett.89.206102
|View full text |Cite
|
Sign up to set email alerts
|

New Structure Model for theGaAs(001)c(4×4

Abstract: The surface structure of the As-stabilized GaAs(001)-c(4 x 4) surface has been studied. We show that the seemingly established three As-dimer model is incompatible with experimental data and propose here a new structure model which has three Ga-As dimers per c(4 x 4) unit cell. This mixed dimer model, confirmed by the rocking-curve analysis of reflection high-energy electron diffraction and first-principles calculations, resolves disagreements in the interpretation of several previous experiments. A good agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
73
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 30 publications
10
73
0
Order By: Relevance
“…Moreover, it should be noted that further 0.5 ML of In adsorption necessary to realize (2×4)α2 on the (4×3) is similar to GaAs(001), where 0.5 ML of Ga changes c(4×4) with Ga-As dimers to (2×4) [14,15]. Ohtake et al found the GaAs(001)-c(4×4) consisting of Ga-As dimers that has been confirmed by ab initio calculations, RHEED, and STM observations [16]. They pointed out that their large-scale STM images from the c(4×4) surface show a conventional brickwork pattern of bright rectangular blocks.…”
Section: Fig 4 Structural Change Sequence Of the Inas(001)-(4×3)mentioning
confidence: 63%
“…Moreover, it should be noted that further 0.5 ML of In adsorption necessary to realize (2×4)α2 on the (4×3) is similar to GaAs(001), where 0.5 ML of Ga changes c(4×4) with Ga-As dimers to (2×4) [14,15]. Ohtake et al found the GaAs(001)-c(4×4) consisting of Ga-As dimers that has been confirmed by ab initio calculations, RHEED, and STM observations [16]. They pointed out that their large-scale STM images from the c(4×4) surface show a conventional brickwork pattern of bright rectangular blocks.…”
Section: Fig 4 Structural Change Sequence Of the Inas(001)-(4×3)mentioning
confidence: 63%
“…Conceivable for example would be an exchange of one of the As atom in the As-As dimer by a N-atom. Such mixed dimer structures have been observed on III-P(001) [6] or InGaP(001) surfaces [7] as well as on GaAs(001) c(4 ¥ 4) surfaces [9]. Upon further annealing of the GaAsN(001) c(4 ¥ 4) to 470 °C the RAS spectra changed gradually to a new line shape.…”
Section: Methodsmentioning
confidence: 88%
“…Here, we define the 1 ML of Ga as the amount of Ga needed to obtain 1 ML of GaAs in the presence of As. At the initial stage, deposited Ga atoms are likely to be incorporated into the arsenic terminated surface to form GaAs, because 1.75 ML of excess As atoms are known to exist on the As-stabilized GaAs(001)-c(4 × 4) surface [22]. Therefore, the remaining 2 ML of Ga atoms give rise to the formation of the droplets.…”
Section: Introductionmentioning
confidence: 99%